Rancangan Mesin Pengayak Pasir dengan Konversi Sistem Gerak Rotasi menjadi Tranlasi - Nanang Endriatno; La Ode Ahmad Barata (Piston: Jurnal Teknologi, 2023)
The development of building construction always requires materials, machines (equipment) and work methods to increase the efficiency of work completion. Sand material which is the main building material in the manufacture of a construction structure. The work method for separation is generally carried out by sieving which aims to obtain uniform sand sizes. In this study, a sand sieving machine was designed using the translation method of shaft rotary motion. Procedures in the design of the sand sieving machine are carried out by collecting initial data and field requirements regarding the sand sieving machine, determining the effective mechanism of the sand sieving machine, analyzing the elements of the sand sieving machine, and determining the design of the sand sieving machine. The working system of the machine is designed to use an electric drive motor, a pulley belt transmission system is used to reduce the rotation of the motor, then the eccentric drive shaft is used to rotate the crank which in turn moves the pusher rod so that the sieve moves translationally. The frame design of this sand sieving machine uses square profile steel 40 mm x 40 mm with a thickness of 2 mm. The box profile steel is designed so that it becomes the support of several machine components including the sieves, the dimensions of the frame are 100 cm long, 70 cm high and 70 cm wide. The calculation results obtained that the shear stress that occurs on the shaft is smaller than the allowable stress. The sieving machine design uses a belt transmission and two pulleys to reduce the motor rotation to 509 rpm, this rotation is then converted into translational motion to move the sieve with a speed of 2.34 m/s.